2008
DOI: 10.1007/s11095-008-9653-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assisted Engineering of Lactose Crystals

Abstract: Ultrasound assisted in-situ seeding, followed by ordered growth in glycerin offers rapid technique for separation of nuclei induction from crystal growth yielding desirable characteristics for better dispersion and in-vitro deposition when employed as DPI carrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 33 publications
7
71
2
2
Order By: Relevance
“…Ultrasound has been widely reported to influence the primary nucleation process accelerating nucleation kinetics, this is typically expressed in terms of reducing the induction time and MSZW [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Ultrasound can also increase the rate of secondary nucleation, this is manifested as a reduction on the product crystal size distribution [20,22,24,31,32,[34][35][36][37][38][39][40][41][42][43]. Ultrasound can also influence crystal growth [20,25,26,36,40,[44][45][46] although the effect on crystal growth is not as dramatic as on nucleation and arises largely from enhanced mass transfer [46] and can influence crystal morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound has been widely reported to influence the primary nucleation process accelerating nucleation kinetics, this is typically expressed in terms of reducing the induction time and MSZW [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Ultrasound can also increase the rate of secondary nucleation, this is manifested as a reduction on the product crystal size distribution [20,22,24,31,32,[34][35][36][37][38][39][40][41][42][43]. Ultrasound can also influence crystal growth [20,25,26,36,40,[44][45][46] although the effect on crystal growth is not as dramatic as on nucleation and arises largely from enhanced mass transfer [46] and can influence crystal morphology.…”
Section: Introductionmentioning
confidence: 99%
“…These include the formation of local hot spots which arise from the large energy release on the collapse of cavitation bubbles creating highly localised regions of extremely high temperature and pressure [50,51], or due to rapid cooling which follows; shockwaves released from cavitation bubbles [52,53], promoting mass transfer and collisions between crystals and adjacent surfaces [54]. These effects of ultrasound on crystallisation have been demonstrated on pharmaceuticals and commodity chemicals including; lactose [35,39,42,55], alpha-dextrose monohydrate [20], glycine [48], p-aminobenzoic acid [47], adipic acid [28], benzoic acid [31], acetylsalicylic acid [27], protein [19] various food products [30,56,57] and in the crystallisation of inorganic materials such as potassium sulphate [26], potassium dihydrogen phosphate [32] and calcite [34]. Ultrasound has also been utilized in continuous crystallisation [28,[58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound application results in a dramatic reduction in induction period, metastable zone width and altered supersaturation conditions. [10][11][12][13] This will have significant effect on co-crystallization process of non-congruent system like caffeine -maleic acid. The sonochemistry reports available to date on co-crystallization of caffeine -maleic acid have used organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Probably the most significant application in this respect is the use of ultrasonic cutting devices. These machines utilize the high-frequency acoustic vibrations (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) to provide a smooth and clean cut for both hard and soft cheeses, minimizing wastage [4,5,56]. Ultrasound has also been commercialized as a method of sealing milk containers and packages of grated cheese -in a process also referred to as ultrasonic welding, the temperature induced by the cavitation processes described above is sufficient to seal the plastic [38,83].…”
Section: Ultrasound In Dairy Processing Applicationsmentioning
confidence: 99%
“…The effects of several experimental conditions on the lactose crystallization process and the lactose crystal properties were investigated: these included the initial lactose concentration, vapor pressure of solution, temperature, ultrasonic frequency, intensity and duration and the presence of inhibitors. Dhumal et al [32] used ultrasoundassisted in-situ seeding for controlling the crystal growth, shape and size of lactose crystals. They suggested that sonocrystallization caused spontaneous supersaturation of lactose, which accelerated the growth of the seeds lengthwise leading to the formation of rod-shaped crystals.…”
Section: Ultrasonic Crystallization and Freezing (Sonocrystallization)mentioning
confidence: 99%